STRATEGI PENINGKATAN KESADARAN MASYARAKAT MELALUI EDUKASI LAMA URAI SAMPAH DI DESA SITUSARI - Sutedi, Ade; Arselia, Seli; Muthoharoki, Oki; Assidiq, Muhamad Imam; Sautan Ali Arrozak; Saputra, Ali Noval; Hermawan, Dani A; Agustin, Andieni Della; Khusaeri Dwi Putra, Rifaldi Al; Natasy, Gea; Agres Firdaus, Mochamad; Muhamad Gery Ms, Akbar; Julia, Nurul; Handiagi, Dede; Fauzan, Yasin Muhamad; Muldani, Ilham Hikmah; Septiani, Anggi; Ahmad (Institut Teknologi Garut, 2025)
Waste is one of the major problems in villages, affecting public health, cleanliness, and tourism potential. The lack of community awareness regarding waste management is largely due to limited access to information and educational media. This community service activity aims to provide a solution through the creation of educational boards as a shared awareness-building medium. The implementation method included field surveys, design planning, production, installation of the educational board at a strategic location near the intersection by SDN 1 Situsari, and socialization of its messages to the community. The results show that the information board successfully attracted residents’ attention and had a positive impact on their cleanliness-related behavior. Strong support from both the community and village authorities further strengthens the sustainability of the program. Through this educational signage, it is expected that community awareness of environmental cleanliness will continue to grow.